Gambaran Faktor Risiko Kontaminan Biologi pada Uji Lingkungan di RSU “Y” Surabaya - Mochamad Rizal Maulana; Khuliyah Candraning Diyanah; Fransisca Susilastuti (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Hospitals as a place of health care and workplace have a variety of potential hazards that can harm health. One of the efforts of the hospital environment can be done by conducting supervision and inspection. The purpose of this research, to describe the risk factors of biological contaminants in the environmental test results conducted in Surabaya General Hospital